THE ANALYSIS OF LOAN REPAYMENT BEHAVIOR ON SHARIA BANKS’ DEBTORS - Soleh, Imron (Al-Infaq: Jurnal Ekonomi Islam, 2017)
The aim of this study is to analyze the debtors‟ behavior of sharia banks. The analysis is based on literature review from various studies related to the case study of sharia banks debtors‟ behavior in Indonesia. The result shows that there are four main aspects of banking behavior, e.g., asymmetric information, character of customer, content of the contract, and monitoring. The customers have high awareness to pay their debt to the bank, unfortunately they need continuous supports from the banks such as intensive monitoring and supervision. Beside these two kinds of support, the banks also need to socialize and warn customers to read the contract carefully. Understanding the contract ('Aqd) is the most important aspect to ensure the financing is repaid well by the customers.